Approximation of solutions of stochastic differential equations with fractional Brownian motion by solutions of random ordinary differential equations - Ral’chenko, K. V.; Shevchenko, H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We prove a general theorem on the convergence of solutions of stochastic differential equations. As a corollary, we obtain a result concerning the convergence of solutions of stochastic differential equations with absolutely continuous processes to a solution of an equation with Brownian motion.